2014
DOI: 10.1371/journal.pone.0096575
|View full text |Cite
|
Sign up to set email alerts
|

Striatal Neurodevelopment Is Dysregulated in Purine Metabolism Deficiency and Impacts DARPP-32, BDNF/TrkB Expression and Signaling: New Insights on the Molecular and Cellular Basis of Lesch-Nyhan Syndrome

Abstract: Lesch-Nyhan Syndrome (LNS) is a neurodevelopmental disorder caused by mutations in the gene encoding the purine metabolic enzyme hypoxanthine-guanine phosphoribosyltransferase (HPRT). This syndrome is characterized by an array of severe neurological impairments that in part originate from striatal dysfunctions. However, the molecular and cellular mechanisms underlying these dysfunctions remain largely unidentified. In this report, we demonstrate that HPRT-deficiency causes dysregulated expression of key genes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 60 publications
0
24
0
Order By: Relevance
“…Our studies have demonstrated a significant deficit of cAMP production in HPRT-deficient cells upon activation with the cAMP agonist forskolin . Additionally, our data further revealed that the deficit in cAMP production in HPRT-deficient cells is accompanied by alteration in protein kinase A (PKA)-related phosphorylation of several phosphoproteins, among them synapsin I, TH, DARPP-32, and CREB (Guibinga et al, 2014;Guibinga & Barron, unpublished data).…”
Section: Mir-181amentioning
confidence: 56%
See 4 more Smart Citations
“…Our studies have demonstrated a significant deficit of cAMP production in HPRT-deficient cells upon activation with the cAMP agonist forskolin . Additionally, our data further revealed that the deficit in cAMP production in HPRT-deficient cells is accompanied by alteration in protein kinase A (PKA)-related phosphorylation of several phosphoproteins, among them synapsin I, TH, DARPP-32, and CREB (Guibinga et al, 2014;Guibinga & Barron, unpublished data).…”
Section: Mir-181amentioning
confidence: 56%
“…We have already reported that Bcl11b expression is markedly downregulated in HPRT-deficient murine neural progenitor striatal cells and in the striatum of adult HPRT-KO mouse as well as in human HPRT-deficient neuron-like cells (Guibinga et al, 2014). Bcl11b is a key transcription factor which drives the expression of a hundreds of striatally enriched genes (Desplats, Lambert, & Thomas, 2008;Tang et al, 2011), among them is PDE10 whose the expression is severely perturbed in HPRT-deficient cells and in the striatum of HPRT-KO mice (Guibinga , Table 1 Cluster of the most significantly upregulated miRNAs in HPRT-deficient human neuron-like cells (differentiated NT2 cells).…”
Section: Bcl11bmentioning
confidence: 95%
See 3 more Smart Citations